An introduction to town planning techniques - Roberts, Margaret (London, United Kingdom : Hutchinson & Co. (Publishers) Ltd., 1974)
This is a book about techniques of planning, written especially for land use planners. It will be useful as an introductory manual for people starting work on a shopping study or a population forecast, and working for examinations.
Preface -- Part 1. Introduction: 1. Introduction-- 2. The land use planning process -- 3. What is planning?-- Part 2. Stages of the land use planning process: 4. Information -- 5. Preliminary analysis -- 6. Models -- 7. Plan design -- 8. Evaluation -- 9. Implementation -- 10. Communication -- Part 3. Land using activities: 11. Population -- 12. Employment -- 13. Housing -- 14. Shopping -- 15. Leisure -- 16. Transport -- 17. Perception.
Includes bibliographical references and index.
Keywords: CITY PLANNING